My issue being with the "... if N is reduced, neither R nor S is reduced. So N and R cannot both be reduced."
I'm not sure why you have an issue with this.
First, I'm pretty sure you would agree that "neither R nor S is reduced" entails "R is not reduced", right? (This is just conjunction elimination.)
Applying this conjunction elimination to the consequent of the implication "if N is reduced, neither R nor S is reduced" then entails "if N is reduced, R is not reduced". I assume you still agree with this, right?
Now, I hope I can convince you that all of the following statements are logically equivalent:
- "if N is reduced, R is not reduced"
- "if R is reduced, N is not reduced" (contrapositive of 1)
- "either N or R is not reduced"
- "N and R are not both reduced" (application of De Morgan's law to 3)
In particular, letting A stand for the statement "N is reduced" and B for "R is reduced", the four statements above can be written using conventional logical symbols as "A ⇒ ¬B", "B ⇒ ¬A", "¬A ∨ ¬B" and "¬(A ∧ B)" respectively.
You can either prove the equivalence of these statements using various deduction rules or just verify that they all have the same truth table:
A |
¬A |
B |
¬B |
A ⇒ ¬B |
B ⇒ ¬A |
¬A ∨ ¬B |
¬(A ∧ B) |
true |
false |
true |
false |
false |
false |
false |
false |
true |
false |
false |
true |
true |
true |
true |
true |
false |
true |
true |
false |
true |
true |
true |
true |
false |
true |
false |
true |
true |
true |
true |
true |
Thus, putting all of this together, "if N is reduced, neither R nor S is reduced" entails "if N is reduced, R is not reduced", which is equivalent to "N and R are not both reduced".
Ps. Perhaps your confusion arises simply from misparsing the statement "N and R are not both reduced" (i.e. "¬(A ∧ B)" using the definitions of A and B above) as "N and R are both not reduced" (i.e. "¬A ∧ ¬B" using the same definitions above). These two statements are indeed not equivalent, with the latter being a much stronger claim.
If so, however, this isn't really an issue of logic, but merely one of English grammar, which does have some ambiguity regarding sentences featuring both negation using "not" and conjunction using "both".
In my opinion, the specific word order in the original solution (and in my statement 4 above) isn't actually ambiguous, since in the phrase "not both" it is clear that the negation by "not" must apply to the conjunction introduced by "both", and not the other way around.
However, similar statements using only slightly different word order, such as "both N and R are not reduced", are indeed ambiguous and could be understood either as "¬(A ∧ B)" or as "¬A ∧ ¬B" depending on context (and possibly the reader's prior expectations). This makes it very easy to misread such sentences if one isn't careful.
And I suspect that some people might even take issue with my claim that "not both" is unambiguous, and claim that in their dialect of English it can mean the same as "both not".
All that said, in the context of the given solution, it should be clear how the combination of "not" and "both" is meant to be understood, since only one interpretation leads to a logically consistent argument. But of course, to see this, you need to at least briefly consider both interpretations before rejecting the obviously absurd one.
In fact (as pointed out by Ben Voigt in the comments below), the example solution itself seems to fall victim to this grammatical confusion when it concludes that (emphasis mine):
"L and N are a pair of areas that cannot both be reduced if both M and R are reduced"
I at least would formally parse this statement, as written, as "(M is reduced ∧ R is reduced) ⇒ ¬(L is reduced ∧ N is reduced)", which is a far weaker statement than what the solution actually proves (and needs to prove!).
The proper conclusion, of course, should be "(M is reduced ∧ R is reduced) ⇒ (L is not reduced ∧ N is not reduced)", which could've been expressed in English e.g. as:
"L and N are a pair of areas that each cannot be reduced if both M and R are reduced"
or perhaps (more closely paralleling the way the question is phrased):
"L and N are a pair of areas neither of which can be reduced if both M and R are reduced"
or even simply:
"neither of L and N can be reduced if both M and R are reduced."
Pps. In your self-answer you write that:
The language is probably more clearly stated as "For N to be reduced R and S must not be reduced.", instead of "If N is reduced, neither R nor S is reduced.", which I read as, "If it is true that N is reduced then it is true that R is not reduced and S is not reduced."
In fact, "For N to be reduced R and S must not be reduced" and "If it is true that N is reduced then it is true that R is not reduced and S is not reduced" are equivalent statements. Indeed, written using logical connectives, both have the exact same form: "N is reduced ⇒ (R is not reduced ∧ S is not reduced)".
The only difference is whether, in English, you read the logical implication "A ⇒ B" as "for A to be true, B must be true" rather than "if A is true, then B is true". But these are just two synonymous ways to state the same logical assertion in English.
Perhaps you're trying to make some distinction about causality with the different phrasings? Or perhaps, given you other remarks such as:
I think this question just doesn't hinge on propositional logic or modes ponens in the way I expected it to.
you might simply have an unreasonably narrow understanding of how propositional logic works.
Indeed, if you limit your available inference rules to pure classical modus ponens (and few if any axioms not given directly in the problem statement), it's quite possible that those tools will be insufficient to solve the problem. For example, while modus ponens allows you to deduce B from A and A ⇒ B, you will need modus tollens to go the other way from ¬B and A ⇒ B to ¬A. Or, alternatively, you would need some way to convert A ⇒ B to its contrapositive ¬B ⇒ ¬A, to which you can then apply modus ponens.
Technically one can prove all valid results of propositional logic using only modus ponens, if one just adds enough logical axioms to emulate all the other inference rules. But that does not seem to be what you're trying to do, either.
Instead, it seems as if you're just trying to apply pure modus ponens directly to the propositions given in the problem statement (not all of which are even in the correct form for it!) without any additional logical axioms (or with just an unstated and apparently quite limited set of such axioms). This is a very weak system of logic (possibly even weaker than minimal logic, depending on what axioms you allow) and unable to prove anything more than the most trivial of syllogisms.